2017
DOI: 10.1103/physrevlett.118.073201
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Engineering of a Low-Entropy Gas of Heteronuclear Bosonic Molecules in an Optical Lattice

Abstract: We demonstrate a generally applicable technique for mixing two-species quantum degenerate bosonic samples in the presence of an optical lattice, and we employ it to produce low-entropy samples of ultracold 87 Rb 133 Cs Feshbach molecules with a lattice filling fraction exceeding 30%. Starting from two spatially separated Bose-Einstein condensates of Rb and Cs atoms, Rb-Cs atom pairs are efficiently produced by using the superfluid-to-Mott insulator quantum phase transition twice, first for the Cs sample, then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…The largest loss in phasespace density occurs in the current setup however already prior to STIRAP due to the low efficiency of Feshbach association. This could be mitigated in an optical lattice [26,27] in the future. Finally we demonstrated that molecules with a dipole moment of 0.54 D can be created in our setup, the most polar diatomic molecular sample so far.…”
Section: Discussionmentioning
confidence: 99%
“…The largest loss in phasespace density occurs in the current setup however already prior to STIRAP due to the low efficiency of Feshbach association. This could be mitigated in an optical lattice [26,27] in the future. Finally we demonstrated that molecules with a dipole moment of 0.54 D can be created in our setup, the most polar diatomic molecular sample so far.…”
Section: Discussionmentioning
confidence: 99%
“…[83] should be able to significantly increase the filling. Similar recent work created a sample of bosonic RbCs Feshbach molecules, at a lattice filling > 30% [84]. There, the Cs was first localized in the MI phase, the Rb was next translated to overlap with the Cs cloud, the lattice depth was then increased further to localize Rb, and finally…”
mentioning
confidence: 99%
“…RbCs Feshbach molecules were created via magnetoassociation, setting the stage to produce groundstate molecules [84].…”
mentioning
confidence: 99%
“…Only a comparatively small fraction of atoms could be converted to heteronuclear dimers because in bulk samples the process is limited by atomic three-body recombination and vibrational relaxation in atom-molecule and molecule-molecule collisions. Such losses can be suppressed if the two atomic samples are overlapped in an optical lattice, creating either a Bose-Fermi Mott-band insulator [42] or a Bose-Bose double-species Mott insulator [38]. In both cases reported so far, a Feshbach resonance was exploited in two different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Second, these molecules are optically transferred into the rovibrational ground state by stimulated Raman adiabatic passage (STIRAP) [26,33,34]. This procedure, which requires precise knowledge of the interand intraspecies scattering properties, has recently led to the production of ultracold and dense samples of heteronuclear molecules such as fermionic KRb [26] and NaK [35] and bosonic RbCs [36][37][38] and NaRb [39] in their rovibrational ground states. The present paper is aimed towards the goal of producing ultracold KCs molecules by similar methods.…”
Section: Introductionmentioning
confidence: 99%